Efficient production of hyaluronic acid by Streptococcus zooepidemicus using two-stage semi-continuous fermentation. (June 2023) - Zhang, Yongjie; Dong, Jinjun; Xu, Guochao; Han, Ruizhi; Zhou, Jieyu; Ni, Ye
Graphical abstract: Highlights: Two-stage semi-continuous fermentation was developed for hyaluronic acid production. High hyaluronic acid titer and productivity can be attained in 2 nd stage bioreactor. Addition of hyaluronidase can reduce viscosity of broth and improve production. Abstract: Hyaluronic acid is a kind of mucopolysaccharide that has wide applications in cosmetics, health food, and orthopedics. Using Streptococcus zooepidemicus ATCC 39920 as parent, a beneficial mutant SZ07 was obtained by UV mutagenesis, giving 1.42 g/L hyaluronic acid in shake flasks. To enhance the efficiency of hyaluronic acid production, a semi-continuous fermentation process consisted of two-stage 3–L bioreactors was developed, in which 1.01 g/L/h productivity and 14.60 g/L hyaluronic acid were obtained. To further enhance the titer of hyaluronic acid, recombinant hyaluronidase Sz HYal was added into 2 nd stage bioreactor at 6 h to reduce the viscosity of broth. The highest hyaluronic acid titer of 29.38 g/L was achieved with a productivity of 1.13 g/L/h at 300 U/L Sz HYal after 24 h. This newly developed semi-continuous fermentation process provides a promising strategy for the industrial production of hyaluronic acid and related polysaccharides.